Intorno a Boccaccio / Boccaccio e dintorni 2017 Atti del Seminario internazionale di studi (Certaldo Alta, Casa di Giovanni Boccaccio, 16 settembre 2017) - Zamponi, Stefano (Studi e saggi, 2019)
The volume Intorno a Boccaccio / Boccaccio e dintorni 2017 arises from the international seminar held in Certaldo on September 16, 2017, promoted by the ENGB National Association and now in its fourth edition. Every year, the seminar aims at giving voice to young scholars, who are invited to present their research, either concluded or current. The volume, together with the contributions on the Decameron, stands out for the attention given to other works by Boccaccio (Buccolicum carmen, Teseida, De casibus virorum illustrium), for the examination of themes which are present in multiple works (Boccaccio and the empire, Homer's biography) and for three contributions focused on the Fortleben of works and themes regarding Boccaccio.